The triumph of labour - Crane, Walter; Schell, Henry (1891)
Engraving; a workers' march, with reference to Greek and Roman mythology and characters Designed to commemorate the international labour day, May 1, 1891, and dedicated to the wage workers of all countries'; 'Hand printed by John G.' PO-1634